Introductory Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-805-X
ISBN 13: 978-0-13417-805-9

Chapter 2 - Test - Page 206: 4



Work Step by Step

3(2y-4)=9-3(y+1) 3(2y)-3(4)=9-3(y)-3(1) 6y-12=9-3y-3 6y-12=-3y+(9-3) 6y-12=-3y+6 6y=-3y+6+12 6y=-3y+18 6y+3y=18 9y=18 y=$\frac{18}{9}$ y=2
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.